O Conselho de Acompanhamento e Controle Social do Fundeb Em quatro Municípios da Região Metropolitana da Grande Vitória - Savergnini, Andre Cibien (2022)
The Monitoring and Social Control Councils that are related to a public fund emerged with the approval of Fundef in 1996. Since their conception to the present day, these collegiates have gained new configurations, first with Fundeb's approval in 2006 and its regulation in 2007 and then with the approval of the permanent Fundeb in 2020. The composition of these collegiates brings together representatives from different segments of society but with focus on education, with the purpose of monitoring the management of these resources. In this work, the objective was to analyze the organization and functioning of the Fundeb’s Monitoring and Social Control in four municipalities in the Metropolitan Region of Greater Vitória: Cariacica, Serra, Vila Velha and Vitória, in view of the possible contributions of these spaces to the improvement of educational public policies and to constitute and/or consolidate as spaces of democratic experience. To achieve this objective, qualitative research was used, a case study using document analysis and semi-structured interviews. As theoretical support, we sought contributions from Chauí (2018), Freire (2001, 2015, 2019a, 2019b, 2020a, 2020b) Gohn (2011), Davies (2008), among others. To obtain the analyzed data, a semi-structured interview was carried out divided into three axes: 1) Characterization of the counselors, their knowledge, and their participation; 2) Organization and functioning of Fundeb Monitoring and Social Control Councils in the municipalities surveyed and 3) CACS Fundeb as a space for the development of Democratic Management and documentary survey produced by the respective councils. Even after the approval of the new legislation, several weaknesses could be observed for the better functioning of these collegiates. The main weaknesses are lack of counselor training, whether initial or ongoing, principally when dealing with technical matters; low representation of civil society in meetings, considering the time schedules they take place, with emphasis on the considerable absence of representation from parents and students; in some cases, lack of infrastructure to carry out on-site visits, lack of replacement by segments of civil society. It is also concluded that the current legislation needs adjustments so that mistakes previously identified are not made again. As a proposition to assist the counselors, we proposed a practical guide aiming to contribute to a better performance of their functions.